MODAL SOSIAL PADA BISNIS ONLINE “WARUNG SEGAR” DI PEKANBARU - Lumbanbatu, Alpia Eva; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Social capital on online busisness “warung segar” in Pekanbaru. This research was conducted at Jalan Garuda Sakti km1, Panam Pekanbaru. The purpose of this study is to find how social capital between owner warung segar with supplier and obstacles experienced in running the “warung segar” online business both online and offline. The research uses descriptive research method. Subjects in this study amounted to 6 people. The technique of the determining the informants is by using purpsosive samping technique. Purposive sampling is taking the subject by setting spesific criteria or characteristic with goal can answer research problems. In collecting data, researchers used observation, interviews and documentation. The theory used is the theory of social capital proposed by Putnam which consists of social networks, social norms and trust. The result of his study are that social capital in its application to the “warung segar” online business very important such as utilizing social relation in maintaning the “warung segar” online business. Social norms are present in the midst of corperation so that can directed and can be as a benchmark. Trust make the “warung  segar” online busisness can survive  to run business. The obstacles faced in carryng out social capital both online and offline are problems that arise between parties who bulid coorperation can not understand about norm so that there are disadvantaged. Keywords: Social Capital. Business Online, Warung Segar